1996
DOI: 10.1128/aem.62.3.1093-1095.1996
|View full text |Cite
|
Sign up to set email alerts
|

Purification and partial characterization of an alkaline lipase from Pseudomonas pseudoalcaligenes F-111

Abstract: An extracellular alkaline lipase of alkalophilic Pseudomonas pseudoalcaligenes F-111 was purified to homogeneity. The apparent molecular weight determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis was 32,000, and the isoelectric point was 7.3. With p-nitrophenyl esters as its substrates, the enzyme shows preference for C 12 acyl and C 14 acyl groups. It was stable in the pH range of 6 to 10, which coincides with the optimum pH range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…zymograms. Other investigators have also reported aggregation of purified lipases to a varying degree [21,[26][27][28]. Application of purified LipA to wells in Spirit Blue agar indicator plates containing an emulsion of tributyrin also indicates activity toward this lipidic substrate (not shown).…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 89%
“…zymograms. Other investigators have also reported aggregation of purified lipases to a varying degree [21,[26][27][28]. Application of purified LipA to wells in Spirit Blue agar indicator plates containing an emulsion of tributyrin also indicates activity toward this lipidic substrate (not shown).…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 89%
“…2 b). LIN et al (1996) and SHARON et al (1998) reported temperature optima of 40 °C and 45 °C for P. pseudoalcaligenes and P. aeruginosa KKA-5, respectively. On the other hand, KOJIMA et al (1994) reported a lipase from P. fluorescens AK-102 with temperature optima of 55 °C and thermostability below 50 °C.…”
Section: Resultsmentioning
confidence: 99%
“…They hydrolyse fats into fatty acids and glycerol at the water-lipid interface and can reverse the reaction in non-aqueous medium ( JAEGER et al 1999). Several alkaline and thermostable lipases exhibiting high activities have been characterized from microorganisms, namely Pseudomonas pseudoalcaligenes (LIN et al 1996), P. fragi (SCHUEPP et al 1997) and P. aeruginosa (SHARON et al 1998). There is an increasing demand for specific lipases ( JAEGER et al 1999).…”
mentioning
confidence: 99%
“…The optimum temperature value is similar to values previously reported for other Pseudomonas sp. lipases [34,35]. The high activity of the ES3 lipase at relatively low temperatures and high pH values suggests that its incorporation into detergent formulations would provide economic benefits to the industry.…”
Section: Effects Of Ph and Temperature On Lipase Activitymentioning
confidence: 99%